The Relationship Between Fast Food Consumption Levels and The Incidence of Anemia In Pregnant Women in the Modern Era at Ujung Loe Public Health - Sari, Iramaya; Risnawati, Risnawati (Hayyan Journal, 2025)
Anemia in pregnant women remains a significant public health problem, both globally and nationally. Data from the World Health Organization (2018) shows that more than 40% of pregnant women worldwide suffer from anemia. In Indonesia, according to the Indonesian Ministry of Health, the prevalence of anemia in pregnant women reaches 48.9% and contributes to the high maternal mortality rate. In the modern era, changes in dietary patterns, particularly the increased consumption of fast food, which is low in iron and high in substances that inhibit nutrient absorption, are thought to play a role in the increased risk of anemia in pregnant women. This study aimed to determine the relationship between fast food consumption and the incidence of anemia among pregnant women at the Ujung Loe Community Health Center, Ujung Loe District, Bulukumba Regency, in 2025. This study used a quantitative analytical design with a cross-sectional approach. A sample of 100 pregnant women in their second and third trimesters was selected using a purposive sampling technique. Data on fast food consumption were collected through a questionnaire, while the incidence of anemia was measured based on hemoglobin levels (Hb <11 g/dL). Data were analyzed using univariate and bivariate methods using the Chi-square test with a significance level of α = 0.05. The results showed that 40% of respondents had high fast food consumption (≥3 times/week) and 35% of pregnant women had anemia. Bivariate analysis revealed a significant association between fast food consumption and the incidence of anemia (p = 0.001). Pregnant women with high fast food consumption had a greater risk of anemia than those with low consumption. It was concluded that there is a significant association between fast food consumption and the incidence of anemia in pregnant women. The results of this study are expected to provide a basis for healthcare professionals to improve education on balanced nutrition and anemia prevention among pregnant women in the modern era.